2004
DOI: 10.2298/mpns0408386p
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies in children with vitiligo

Abstract: Several studies have shown a significant incidence of positive autoantibodies in children with vitiligo, compared to children without vitiligo. However, in our series, presence of ANA, ATA, APCA, SMA, ACA and AMA was not significantly increased in children with vitiligo, compared with children without vitiligo. Further studies are necessary in this area in order to draw more conclusions. In the previous studies, it has been established that children with vitiligo were generally healthy, whereas adults with vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 8 publications
2
7
0
Order By: Relevance
“…The present study provides indirect evidence that human CD8+ T cells release IFN-γ. The in vitro study of Cho 2000 et al [29] also demonstrated that human MHC class I restricted CD8+ T cells specific for Mtb protein epitopes contribute to host defense by the release of IFN-γ, by lysing infected target cells, and by directly killing the intracellular bacteria. Claudia 2006 et al [30] also documented that CD8+ T cells control Mtb infection in healthy house hold contacts of TB patients.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The present study provides indirect evidence that human CD8+ T cells release IFN-γ. The in vitro study of Cho 2000 et al [29] also demonstrated that human MHC class I restricted CD8+ T cells specific for Mtb protein epitopes contribute to host defense by the release of IFN-γ, by lysing infected target cells, and by directly killing the intracellular bacteria. Claudia 2006 et al [30] also documented that CD8+ T cells control Mtb infection in healthy house hold contacts of TB patients.…”
Section: Discussionmentioning
confidence: 99%
“…It has been documented that IFN-γ and tumor necrosis factor-α play role in the induction of inducible nitric oxide synthase and nitric oxide [22,23]. In an earlier work, specific mycobacterial antigens like ESAT6 and CFP-10 were used to stimulate IFN-γ production [24].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations